Epizootological and epidemiological situation of anthrax in Siberia and the Far East (1985–2023) - Z. F. Dugarzhapova; E. V. Kravets; S. V. Balakhonov (Acta Biomedica Scientifica)
Anthrax remains relevant in the world and in the Russian Federation. In Siberia and the Far East, epizootological, epidemiological, environmental and microbiological monitoring of anthrax is constantly carried out. To analyze the epizootological and epidemiological situation of anthrax, we used the information from veterinary institutions and Rospotrebnadzor for 24 regions, as well as reference and archive materials. On the territory of Siberia and the Far East for the period from 1985 to 2023, pronounced epizootological and epidemiological problems of anthrax are observed in the Yamalo-Nenets Autonomous Okrug, the Republic of Buryatia, Omsk Region and the Altai Territory. Over the last five-year observation period, high epizootic activity has been observed in the west of the Republic of Tyva. A total of 3,375 livestock animals and 128 people fell ill. The anthrax database contains information on 7,491 stationary anthrax-infected points in 22 subjects and 562 anthrax burials and cattle burials in 17 subjects of Siberia and the Far East. B. anthracis strains have slight variability in biological properties and belong to two global genetic lines – A and B. In order to prevent anthrax, it is necessary to ensure surveillance of soil foci of anthrax (anthrax burials and cattle burials, “plague fields”), a high level of livestock animals registration and their specific vaccination coverage; to control the implementation of veterinary and sanitary requirements for pre-mortem inspection and emergency slaughter of livestock, the sale of meat and meat products, and biological waste disposal; to carry out explanatory work among the population.